URGENCY OF THE DRAFT STATUTE ON MATERNAL AND CHILD WELFARE FOR FEMALE EMPLOYEES - Nisa, Ardina Khoirun (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2023)
The ongoing deliberations involve the Draft Statute on Maternal and Child Welfare, with particular emphasis on several regulations that prioritize the well-being of mothers and children. This study emphasizes the initial 1000 days of an individual’s life, commencing from the prenatal stage, commonly referred to as the